App-assured essential physical activity for the prevention of cognitive decline: changing paradigms in public health – a study protocol for a randomised controlled trial: A study protocol of the PA PROTECT study - Jamka, Małgorzata; Makarewicz, Aleksandra; Wasiewicz-Gajdzis, Maria; Brylak, Jan; Wielińska-Wiśniewska, Hanna; Pawlak, Zuzanna; Nowak, Jan Krzysztof; Herzig, Karl-Heinz; Mądry, Edyta; Walkowiak, Jarosław (Journal of Medical Science, 2021)
This study aims to assess the effect of an increase in daily physical activity to prevent cognitive decline, sustain brain volumes and maintain healthy biomarker levels in mild cognitive impairment (MCI) subjects aged 50-70 years. In total, 198 subjects with MCI (assessed using the Montreal Cognitive Assessment test) will be recruited and randomised into two groups: active and passive. The active group will be instructed, encouraged and motivated to increase their physical activity to at least a moderate level (≥ 10,000 steps/day), whereas the passive group should maintain their normal activity levels. All subjects will undergo cognitive assessment, neuroimaging and biomarker tests prior to and after a one-year intervention. During the intervention, physical activity will be measured by the Fitbit Inspire HR wristband. The study was registered in the German Clinical Trials Register database (registration no. DRKS00020943, date of registration: 09.03.2020, protocol version: 1.0).